The Use of Fresh Pomegranate Juice in the Treatment of Covid-19: Clinical Case Study - Alkhatib, Ahed J (PSM Biological Research, 2021)
Since its discovery, COVID-19 has changed and reshaped our lives, and scientists and researchers are competing to find out therapeutic options and vaccines. The main objective of the present study was to report our experience in treating three cases that proved positive by polymerase chain reaction (PCR) by fresh juice of pomegranate in different therapeutic models of COVID-19 treatment. The first case was a male aging 56 years. He was instructed to use fresh pomegranate juice as a preconditioning model to protect him against the possibility of exposure to COVID-19. His family later were infected by a coronavirus in addition to him. His disease passed unnoticed in comparison with the remaining members of his family. The second case was a female, 64 years, who was hospitalized for being positive for COVID-19 by PCR. She had severe symptoms associated with corona and her oxygen saturation was as minimal as 50% and the ventilator was required. Her family members decided that their mother is best in her home instead of the hospital as far as they can obtain an oxygen ventilator. Her sons were instructed to give her fresh pomegranate juice. The first impression was that her oxygen saturation increased to above 90%. After 5 days, she was in a good health and tested for COVID-19 by PCR, and the result was negative. The third case was positive for COVID-19 and had lung fibrosis. Her oxygen saturation was as minimal as 40% and its beak was 80% using a ventilator. After using one liter of fresh pomegranate juice, she had become in a good health and her oxygen saturation percent reached 98%. The use of fresh pomegranate juice is a promising therapeutic approach for COVID-19 and can be developed as a formal therapeutic for COVID-19 by pharmaceutical companies.